PENGARUH FERMENTASI KULIT KOPI DENGAN KAPANG Pleurotus ostreatus DAN Lentinus edodes TERHADAP PROTEIN KASAR DAN SERAT KASAR : EFFECT OF COFFEE SKIN FERMENTATION WITH MOLDS Pleurotus ostreatus AND Lentinus edodes ON CRUDE PROTEIN AND CRUDE FIBER - Amran, Muhammad; Kamal, Mustafa; Trisna, Ade; Rajina, Meli; Husen, Firdaus; Maulana, Fajri (Tropical Animal Science, 2025)
This research aims to determine the effect of coffee skin fermentation with the molds Pleurotus ostreatus and Lentinus edodes on crude protein and crude fiber. The research method used was an experimental method with a Completely Randomized Factorial Design (CRDF), consisting of Factor A: Differences in Microorganisms, namely A1: Lentinus edodes and A2: Pleurotus ostreatus, while Factor B: Difference in length of fermentation days, namely B1: 3 days , B2: 6 days and B3: 9 days. Each treatment was repeated 3 times. The variables observed were the quality of crude protein (%) and crude fiber (%). The results of this research were that there was no interaction (P>0.05) between the type of microorganism and the length of fermentation days. Meanwhile, each factor had a very significant influence (P<0.01) in improving the quality of coffee skin. The conclusion of this research is that fermented coffee skins using Lentinus edodes mold with a fermentation time of 9 days provide the highest increase in crude protein and the lowest decrease in crude fiber. The crude protein content value was found to be 19.86%, while the crude protein of the coffee skin before fermentation was 11.16%. The crude fiber content of the coffee skin after fermentation with Lentinus edodes was 15.42%, while the crude fiber content of the coffee skin before fermentation was 26.31%.